In-Hospital Mortality Following Traumatic Brain Injury Among Older Medicare Beneficiaries, Comparing Statin Users With Nonusers. (December 2017) - Khokhar, Bilal; Simoni-Wastila, Linda; Slejko, Julia F.; Perfetto, Eleanor; Zhan, Min; Smith, Gordon S.
Background: Traumatic brain injury (TBI) is a significant public health concern for older adults. Small-scale human studies have suggested pre-TBI statin use is associated with decreased in-hospital mortality following TBI, highlighting the need for large-scale translational research.Objective: To investigate the relationship between pre-TBI statin use and in-hospital mortality following TBI.Methods: A retrospective study of Medicare beneficiaries 65 and older hospitalized with a TBI during 2006 to 2010 was conducted to assess the impact of pre-TBI statin use on in-hospital mortality following TBI. Exposure of interest included atorvastatin, fluvastatin, lovastatin, pravastatin, rosuvastatin, and simvastatin. Beneficiaries were classified as current, recent, past, and nonusers of statins prior to TBI. The outcome of interest was in-hospital mortality. Logistic regression was used to obtain odds ratios (ORs) and 95% confidence intervals (CIs) comparing current, recent, and prior statin use to nonuse.Results: Most statin users were classified as current users (90%). Current atorvastatin (OR = 0.88; 95% = CI 0.82, 0.96), simvastatin (OR = 0.84; 95% CI = 0.79, 0.91), and rosuvastatin (OR = 0.79; 95% CI = 0.67, 0.94) use were associated with a significant decrease in the risk of in-hospital mortality following TBI.Conclusions: In addition to being the most used statins, current use of atorvastatin, rosuvastatin, and simvastatin was associated with a significant decrease in in-hospital mortality following TBI among older adults. Future research must include clinical trials to help exclude the possibility of a healthy user effect in order to better understand the impact of statin use on in-hospital mortality following TBI.